Budidaya Sayur Secara Hidroponik dan Ikan Lele dengan Teknologi BioMaxi untuk Memupuk Jiwa Enterpreneurship - Rosmaiyadi Rosmaiyadi; Slamat Fitriyadi; Susan Neni Triani (Jurnal Pemberdayaan Masyarakat, 2019)
Developing entrepreneurship for the students should be done starting from of primary and secondary education. The major obstacles experienced by the school in general are not the inclusion of entrepreneurial material in the curriculum contained in the school subjects. Similarly, the partner in this case MTs Al Fatah Singkawang. The constraints that the partners of the community service Program are the limitation of capital (cost), human resources, technology and also the location of land that is narrow enough to implement activities for students. Program activities are conducted with hydroponic vegetable cultivation and catfish cultivation with Bioflok technology which is carried out by 30 students MTs Al Fatah and also involve the practitioners of hydroponic vegetable cultivation and also fish farming practitioners Catfish with Bioflok system. This activity was held from May 2019 until December 2019. Hydroponic vegetable farming and catfish cultivation activities with Bioflok technology started with the preparation of cultivation media until the process of cultivation. Results show that students can already practice vegetable cultivation in hydroponics and fish farming with BIOMAXI technology and this activity plays a major role in cultivating the entrepreneurship of students.